On Barcilon’s formula for Krein’s string - Kac, I. S.; Pivovarchik, V. N. (Methods of Functional Analysis and Topology, 2017)
We find conditions on two sequences of positive numbers that are sufficient for the sequences to be the Neumann and the Dirichlet spectra of a Krein string such that Barcilon’s formula holds true.